Karoula, Maria - (:unkn) unknown (My University, 2026)
Maria Karoula is a Special Scientist (German Language) at the Language Centre of Cyprus University of Technology. She completed her studies in German Philology, History of the German Literature and the Political Sciences at the Philosophy Faculty of the Rheinisch-Westfälische Technology University of Aachen in Germany. At the same University she has completed an MA Degree ( Magistra Artium) in Linguistics .Her graduate work focused on the “ Dialect and Official Language. Difficulties of the dialect speakers at the proses of learning the official language”. She has worked as a teacher of German language at the private College “The CTL Eurocollege”, at different private Language Institutes, at the Government Educational Institutes of Limassol and at the Government Secondary Education (with contract) in many Lyceums of Cyprus. She has also worked at the Ministry of Education and Culture of Cyprus as Advisor of German language. She has taken part to educational seminars organized by the Ministry of Education, the Association of Teachers of German Language and the Goethe Institute. These seminars concern new teaching methods. She is a foundation member and the Secretary of the Association of the Teachers of German Language and Philology.